A COMPARATIVE ANALYSIS OF INTERNATIONAL STANDARDS AND PRACTICES IN ENGINEERING EDUCATION - Alimov Azam Anvarovich (Bright Mind Publishing, 2025)
Background. Petroleum engineering education is under pressure to deliver structured, competency-based curricula aligned with international standards and fast-evolving industry needs. Objective. To compare level-based teaching approaches and competency frameworks in petroleum (and closely allied energy/resources) programs across the European Union, the United States, Japan, and South Korea, and to distill actionable models for competency mapping and curriculum design.
Keywords: Petroleum engineering education; competency mapping; curriculum design; ABET; EUR-ACE; JABEE; ABEEK; level-based learning; CDIO; PBL